2010
DOI: 10.1002/edn.163
|View full text |Cite
|
Sign up to set email alerts
|

Body image, intimacy and diabetes

Abstract: or monitoring blood glucose excessively, result in suboptimal diabetes control. Therefore, it is essential, that treatment interventions reduce body image distress by integrating both psychological and diabetes-related factors. Do not be afraid to ask patients about the role they believe diabetes plays in their relationships. Conflicts of interestNone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Results from previous studies have been inconclusive as to whether adolescents with T1D are more likely to have body image problems compared with other adolescents. Several researchers found that youths with diabetes more frequently reported concerns and dissatisfaction about their bodies ( Colton et al, 1999 ; Neumark-Sztainer et al, 2002 ; Kichler et al, 2008 ; Shaban, 2010 ; Kaminsky and Dewey, 2013 ; Philippi et al, 2013 ; Pinquart, 2013 ; Kaminsky and Dewey, 2014 ; Troncone et al, 2016 , 2018 ). In contrast, and more in line with the findings of this study, other studies have found no significant differences in body image problems between adolescents with T1D and healthy peers ( Striegel-Moore et al, 1992 ; Meltzer et al, 2001 ; Ackard et al, 2008 ; Kaminsky and Dewey, 2013 ; Falcão and Francisco, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from previous studies have been inconclusive as to whether adolescents with T1D are more likely to have body image problems compared with other adolescents. Several researchers found that youths with diabetes more frequently reported concerns and dissatisfaction about their bodies ( Colton et al, 1999 ; Neumark-Sztainer et al, 2002 ; Kichler et al, 2008 ; Shaban, 2010 ; Kaminsky and Dewey, 2013 ; Philippi et al, 2013 ; Pinquart, 2013 ; Kaminsky and Dewey, 2014 ; Troncone et al, 2016 , 2018 ). In contrast, and more in line with the findings of this study, other studies have found no significant differences in body image problems between adolescents with T1D and healthy peers ( Striegel-Moore et al, 1992 ; Meltzer et al, 2001 ; Ackard et al, 2008 ; Kaminsky and Dewey, 2013 ; Falcão and Francisco, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, there is no general agreement that body image problems are always reported in youths with T1D. Specific elements of the illness and its treatment, -i.e., dietary restrictions, recurring weight variation, the subjective perception of living in an unhealthy body, focus and attention on the body, daily need for injections, etc.- are thought to facilitate the development of a negative body image ( Colton et al, 1999 ; Shaban, 2010 ). Greater body dissatisfaction and an attitude toward body image problems have been reported in several studies on adolescents and young adults with T1D ( Neumark-Sztainer et al, 2002 ; Kichler et al, 2008 ; Kaminsky and Dewey, 2013 , 2014 ; Pinquart, 2013 ; Troncone et al, 2016 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, there were 5 million deaths due to diabetes and the cost of diabetes that year was in excess of $US50 million ( Cho et al, 2018 ). Empirical research demonstrates that body image is strongly associated with depression ( Carroll et al, 1999 ; Ali et al, 2006 ), poorer treatment adherence ( Carroll et al, 1999 ; Ritholz et al, 2010 ; Chao et al, 2012 ), and DM-related complications ( Shaban, 2010 ; Williams et al, 2011 , 2013 ; McDonald et al, 2014 ). While the presence of complications can cause clear objective and visible bodily changes, such as amputation, many people with diabetes do not have observable change in appearance as a result of their illness.…”
Section: Introductionmentioning
confidence: 99%
“…There is recent evidence describing individuals with diabetes characterised by low resilience, positively associated with maladaptive coping strategies and diabetes-related distress (Yi-Frazier et al, 2013), and by high health anxiety, negatively associated with quality of life and adherence to diabetes self-care activities (Janzen Claude et al, 2014). Some studies pointed out that the specific factors connected to the illness and its treatment (dietary restrictions, real weight variation with possible changes in the perception of body size, the notion of living in an unhealthy body and need for injections) may contribute considerably towards the development and persistence of a negative body image in individuals with type 1 diabetes (Colton et al, 1999;Shaban, 2010).…”
Section: Introductionmentioning
confidence: 99%